A soil moisture‐based framework for guiding the number and location of soil moisture sensors in agricultural fields. Issue 6 (20th September 2021) - Rossini, Pedro R.; Ciampitti, Ignacio Antonio; Hefley, Trevor; Patrignani, Andres
Abstract: Soil moisture information is a key variable for guiding in‐season management decisions in rainfed and irrigated agricultural systems. However, methods for deciding the number and location of soil moisture sensors (SMS) per field still remain poorly explored in the scientific literature. The goal of this study was to evaluate a quantitative framework based on soil moisture‐based management zones (MZs) to determine the minimum number and tentative deployment location of SMS. Multiple spatially intensive ( n > 100 observations) surveys of near‐surface (0–12 cm) soil moisture were conducted during the fallow periods and early growing seasons of 2017, 2018, and 2019 on three agricultural fields using a calibrated handheld soil water reflectometer. The fuzzy C ‐means (FCM) clustering method was used to delineate MZs based on the soil moisture surveys, and the silhouette clustering evaluation method was used to identify the optimal number of MZs per field. Then, a sensor location index that considered the distance to the MZ boundaries and the FCM membership grade was developed to identify the tentative optimal deployment location of SMS. The proposed method effectively identified field areas with distinct soil moisture regimes and revealed the complex soil moisture spatial patterns that were not captured with elevation or soil texture alone. Dividing the fields using soil moisture‐based MZ reduced the intrazone soil moisture spatial variability by about 50% compared with that of the entire field. In the three studied fields, a total of two SMS were sufficient to capture the salient soil moisture spatial regimes. Core Ideas: Field surveys of near‐surface soil moisture were used to delineate management zones. Soil moisture‐based management zones were used to find the number and location of sensors. Two soil moisture‐based management zones captured the salient soil moisture spatial patterns. In situ soil moisture observations revealed spatial patterns not evident with proxy variables.